Phrasal verbs-related problems that intermediate intensive English ii students of the Foreign Language Department, at the University of El Salvador, semester I, 2016 have in terms of semantic comprehension - Orellana, María Antonia
Since the learning of two-word and three-word phrasal verbs has become a problem for non-native students, and even more for those who have no grammatical equivalent on their mother tongue, the process of learning phrasal verbs becomes challenging not only for the reason already mentioned but for the fact that there are phrasal verbs that have more than one meaning depending on the context and also their own grammatical structure, as well as the different complications that a teacher could find when teaching phrasal verbs, and the difficulties for students to use this kind of compound verbs, adding some resistance to use phrasal verbs using single-word verbs instead. The present project makes reference to the current state of Intermediate Intensive English II students, semester I, 2016 from the Foreign Language Department (FLD) at the University of El Salvador. This research is focused on three aspects mainly. First, it is focused on identifying which the most common phrasal verbs-related problems are on Intermediate Intensive English II students, semester I, 2016 in terms of semantic comprehension when reading; second, it is designed to find out which the most effective techniques are that teachers from FLD can use to overcome these phrasal verbs-related problems; and third, it pretends to recommend some techniques to FLD so that phrasal verbs-related problems can be solved and improve students’ semantic comprehension.